Enhancement modules for Cocos2d and Box2d game engines used in educational mobile games development - Asis, Adrian Mikko M.; Cartagena, Angela Felicia S.; De Guzman, Rachelle Anne S.; Demetria, Johanne Oliver D.; Florentino, Maria Cecilia M.; Padilla, Danielle P. (2011)
Mobile educational games are now being utilized as a platform for supplementary education. In line with the Grade Six science curriculum as mandated by the Department of Education, lessons like Pollution, Types of Forces, Newton's Third Law, Constellations, Color and Temperature of Stars and Earthquakes are used in the development of games. Science based games offer a wide range of possible game plays based on its dynamic content. Different game genres could be used to be able to cater to the goal of educational games which is to allow for play and learning to take place simultaneously. The current trend is to use game engines, which serve as a framework for game creation. Cocos2D for iPhone is a game engine for the Apple iOS platform. It has several features like scene management, sprites, and incorporation of physics engines which allows for easier game creation, since developers would have more focus on the content as opposed to the implementation of the content. Box2d is a physics engine that can be integrated with Cocos2D. This allows for basic Physics events to be abstracted and handled by Box2d instead of the developer scheduling callbacks and performing computations. Although both Cocos2D and Box2d are enough to be able to create games, enhancements are needed in order to address for developing more complex games that cater to different game genres. This project then focuses on the development of enhancement modules so as to implement the desired action and events needed for the science based educational games. These modules would be tested for its functionality and performance prior to its incorporation to actual developed games. The developed games would then serve as the main testing interface for the enhancement modules. Part of the evaluation process is to let students evaluate the games and determine if the enhancement modules are able to function based on their initial design.